An Object in the Italian Renaissance Art. Artifact and Art-Object - Makho, Olga G. (Actual Problems of Theory and History of Art, 2017)
The categories of “artifact” and “art object”, on which the conference is focused, are relatively young in the theory and history of fine arts. They have been existing mainly due to the processes that characterize the general situation in actual art. It should be said though that the phenomena described with these categories had been born much earlier. Like much in European cultural tradition, their emergence dates back to the Renaissance. It was then that understanding of the sphere now known as the sphere of fine arts crucially changed. Same as fine arts, the applied arts passed through notable secularization, and it was then that the contemporary idea of collecting as of specific activity was formed. For a long time the author has been studying the material discussed in the article, and turned to it repeatedly, considering it in various aspects. In the given case the material for the first time is put into a new terminological context. Objects like natural curiosities, or things that have nothing in common with the high sphere of fine arts, when placed into Isabella D’Este’s Grotta together with art works from Classical Antiquity and creations of outstanding craftsmen of later periods, are qualified as artifacts. In the same way are treated the images of, for instance, unique musical instruments, executed in tarsia technique in the decorative panel of Federico da Montefeltro’s studiolo at the Duke’s palace of Urbino, while the cabinet itself, with its exceptionally perfect programme and its brilliant picturing, is understood as an art-object.